Psychological richness can enhance innovative behavior of Chinese college students: the chain mediating role of cognitive flexibility and creative self-efficacy - Yu, Peilin; He, Aiyao; Wang, Qinyan; Li, Yutang; Hu, Si; Gao, Yuwei (Frontiers in Psychology, 2025)
To investigate the relationship between psychological richness and innovative behavior among Chinese college students, as well as the roles of cognitive flexibility and creative self-efficacy in this relationship, this study employed the Psychologically Rich Life Questionnaire, Cognitive Flexibility Scale, Creative Self-Efficacy Scale, and Innovative Behavior Scale to survey 669 Chinese college students. The results show that: (1) Psychological richness positively predicts innovative behavior; (2) Cognitive flexibility and creative self-efficacy, respectively, play a partial mediating role between psychological richness and innovative behavior; (3) Cognitive flexibility and creative self-efficacy play a chain mediating role between psychological richness and innovative behavior. The findings enrich the research results in the field of innovative behavior among Chinese college students and provide enlightenment for the cultivation of innovative talents in Chinese higher education.